2009
DOI: 10.1021/bi900154f
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Dynamics, and Activity of an All-Cysteine Mutated Human β Defensin-3 Peptide Analogue

Abstract: Human beta defensin-3 (HBD-3) is a unique potent antimicrobial peptide. To explore the importance of the three-dimensional structure of HBD-3 in its activity and selectivity, we have mutated all six cysteine residues of HBD-3 to other amino acids, expressed the mutant (named as Def-A) in Escherichia coli, and analyzed the mutant's activity, structure, and dynamics. Def-A is active against several bacterial strains, but the activity is influenced by the ionic strength of the environment. When subjected to vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The corresponding spectrum for reduced TC-1 showed a much less pronounced profile, indicating major unfolding and supporting the NMR results. Given that many antimicrobial peptides change conformation upon binding to their target membranes (8,15), the structures of native and reduced TC-1 were also measured in the presence of SDS micelles. The CD and proton NMR spectra for TC-1 indicate that its native ␤-sheet structure converts into more ␣-helical elements in the presence of the detergent micelles, with the CD profile showing the prominent double minima at 208 and 222 nm characteristic of ␣-helical structures (Fig.…”
Section: Design Of Tc-1 Substitution Variants Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding spectrum for reduced TC-1 showed a much less pronounced profile, indicating major unfolding and supporting the NMR results. Given that many antimicrobial peptides change conformation upon binding to their target membranes (8,15), the structures of native and reduced TC-1 were also measured in the presence of SDS micelles. The CD and proton NMR spectra for TC-1 indicate that its native ␤-sheet structure converts into more ␣-helical elements in the presence of the detergent micelles, with the CD profile showing the prominent double minima at 208 and 222 nm characteristic of ␣-helical structures (Fig.…”
Section: Design Of Tc-1 Substitution Variants Withmentioning
confidence: 99%
“…Moreover, reduction and unfolding are even required to reveal the full antimicrobial activity of human ␤-defensin 1 (13). Upon linearization, these proteins can lose their characteristic ␤-sheet secondary structures (14,15) that will substantially affect their three-dimensional structure (16). These observations question the necessity of the three-dimensional positive patch for antimicrobial activity and suggest that other structural elements, at least in the linearized proteins, are involved in this antimicrobial activity.…”
mentioning
confidence: 99%
“…V (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) results in a significant loss of activity. This decrease in sensitivity is not wholly dependent on the Gram status of the bacteria, since Gram-negative E. coli ATCC 25922 shows sensitivity to Defb14-1C V ⌬(1-11) in a pattern similar to that of Gram-positive S. aureus species.…”
Section: Defb14-1cmentioning
confidence: 99%
“…Further work using modifications of this decapeptide sequence has shown that its antimicrobial activity is more complex than just being a function of charge (13). In addition, work on an hBD3 derivative where the cysteines of the full-length mature peptide are changed to alanines has revealed that this peptide is as active as the parent peptide against Gram-positive and -negative bacteria but is now sensitive to the ionic strength of the medium (3). As the cysteine content of the peptide does not affect the antimicrobial activity of the peptide, we have focused on the Defb14-1C V analogue (20).…”
mentioning
confidence: 99%
“…hBD analogs that differ in structural characteristics from the wild-type peptides appear to preserve their antimicrobial activities (8)(9)(10). This finding prompted a race to design hBD analogs potentially endowed with therapeutic properties (9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%